KHOI-TANBA: WORLDVIEW OF CHASING BEES AND WASP AWAY BY THE KHURKHULS OF MANIPUR - Singh, Ngathem Pungfa; Singh, Thiyam Rabikanta; Singh, Kh. Bimol (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This field work based paper is the outcome of the anthropological study conducted in the Khurkhul village of Manipur where the ‘Khoi-tanba’, is performed as a way of warding off the evils from causing death and miseries in the family. ‘Khoi-tanba’, literally meaning chasing the bees/wasp away, in Manipuri language, is an aged old magico-religious practice of the ‘Meiteis’ still performed by the ‘Khurkhuls’ in the Khurkhul village in Manipur with the help of a ‘Maiba’, a male religious leader authorised for sacred performances and also a traditional healer on the belief that the presence of a typical bee hive/s (but not of the honey bees) in someone’s homestead particularly on the Northern or the ‘Awang’ side of the house will bring inevitable death in the family. Getting rid of giant bees and wasp is a means of getting rid of psychological fears from causing havoc in the family and to relief from the apprehension of damaging their mental health conditions. The main objective of studying the cult of ‘Khoi-tanba’ is to understand their traditional ways of preventive measures towards mental health. The Khurkhuls are much concerned about their health and the concept of health among them is not just the mere absence of diseases. All that activities for seeking good health as well as the treatment of already afflicted ones requires both modern and traditional practices. It is evident that physical well-being and mental satisfaction are two sides of the same coin: one cannot live a healthy life without honouring the mental aspect. The present study adopted standard techniques of modern ethnographic research such as Observation, Case study and Interview. The primary data were collected from the traditional health practitioners or the ‘Maibas’ as well as members of the households in question. The results of the study indicated that ‘Khoi-tanba’ cannot be performed on any day but only on the specific days of the particular month known as the ‘tatnaba numit’ because it is not considered to be an auspicious occasion as per their schemas. Further, it also involves the leaves of the sacred ‘tairen’ (Toona ciliata) and hymns chanted by the ‘maiba’ to avoid miseries from multitudes of spirits in mischief.